ANALISIS PENGARUH MARKETING ACTIVITY DAN WORKING CAPITAL TERHADAP PROFITABILITAS DI PT. KRAKATAUSTEEL TAHUN 2010-2018 - LMS Kristiyanti; Abdul Haris Romdhoni; Alfiana Kristi (ITB AAS INDONESIA, 2019)
This observation is aimed to know that there is influence between marketing activity and working capital to profitability in PT. KRAKATAUSTEEL. This uses trimester financial statements from the last trimester financial statement in 2010 until first trimester financial statement in 2018 as samples in observation.This is a quantitative observation in which it uses 1 population and 30 samples in total. This uses secondary data as source which is downloaded from official website of company and some websites establishing its information. The technique in collecting data is a non-participant observation which doesn’t require researcher to work financial statements out directly. This observation uses multiples linear regression analysis. The result of observation shows that there is not any influence between marketing activity (which represented by marketing expense, company size and company age) and profitability partially in PT.KRAKATAUSTEEL year of 2010 to 2018, however it shows that working capital influences profitability in PT. KRAKATAUSTEEL year of 2010 to 2018 partially. As for the result in simultan, both of marketing activity and working capital has influence to profitability. Keywords : marketing expense, company age, company size, working capital, profitability